A supply chain analysis of honey in region XI - Sioson, Noren Mae S. (2009)
Honey production is one of the high potential activities of apiculture or beekeeping. The general objective of this study was to examine the supply chain of honey in Region XI. The supply chain of honey in Region XI is mainly composed of beekeepers directly selling to the end consumers. It is said that there is a high demand for the honey product in the region but its local supply can not meet the said demand. The beekeepers cited that other external factors are the lack of foraging areas in Davao Region and the vast spraying of chemicals and insecticides for they harm and kill the bees. It affects the ability of the honey bees to generate high quality honey products. Furthermore, as observed in the data gathering process, only a few beekeepers are actually involved in the business of selling honey even experts say that Mindanao is an appropriate area for beekeeping due to its climate. Difficulties were also encountered in collecting accurate and good quality data since most of them has not actually done formal recording of their operations. Given this situation, it can be observed that honey industry has indeed, not yet reached its full potential as an industry in Region XI. Thus, the study would recommended the expansion of agricultural areas that could be suitable locations for beekeeping. In addition, the exploration of the presence of consolidations can also be significant for the improvement of the industry. Conducting of trainings and seminars must also be continued in order to maintain the awareness of potential investors, processors and ed users regarding the product.
Thesis, Undergraduate (BS Agribusiness Economics) -- U. P. in Mindanao